Antibacterial Activity of Jojoba Seed residue and Its Possible Active Compound - Irmanida Batubara; Arnold Patogi Siahaan; Eti Rohaeti; Ali Mahmoud Muddathir (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Jojoba (Simmondsia chinensis) (Link) C.K. is a shrub plant widely used in cosmetics, especially jojoba oil. The residue will remain when producing jojoba oil and become waste. This study aimed to determine the antibacterial activity of Jojoba seed residue (JSR) and its possible active antibacterial compounds. JSR was collected from Sudan and extracted by maceration with n-hexane, ethyl acetate, and 70% ethanol. The antibacterial activity was determined with the microdilution method against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). The 70% ethanol extract showed the value of MIC and MBC against E. coli, which was 7.8 mg/ml; meanwhile, against S. aureus was 3.9 mg/mL and 7.8 mg/mL, respectively. Fractionation of 70% ethanol extract using silica gel column chromatography with gradient elution produced ten fractions. Fraction 3 showed the MIC and MBC values in E. coli which were 3.1 mg/mL and 12 mg/ml, and in S. aureus, which were 3.1 mg/mL and 6.2 mg/mL. The fractionation continued to Fraction 3 using preparative thin layer chromatography to collect subfraction 3.2 at an Rf value of 0.76, actively based on contact autobiography against E. coli and S. aureus. Embelin was detected in Subfraction 3.2 using liquid chromatography-mass spectrometry (UHPLC-Q-Orbitrap HRMS) and suggested as the active antibacterial component in JSR.